On the impossibility of phenomenology - Alliez, Eric; Gallimard, Joëlle (Estudios de Filosofía, 1999)
The article makes a presentation of French philosophy from the vantage point of the contemporary horizon created by it. Decisive for this contemporariness are both the development given to phenomenology (phenomenological tradition in French phenomenology) and its problematic nature. Due to the latter, phenomenology has been taken to its most extreme possibilities (either phenomenology is only possible as ontology, or ontology is only possible as phenomenology), in order to determine how the demand of which it is a bearer imposes its being assumed as possible in its pure impossibility, an impossibility that gives evidence of the urgency of new images for thought